Penerapan Nilai-Nilai Kitab Adabul ‘Alim Wal Muta’allim Dalam Pembentukan Akhlak Siswa - Achmat Muchibin; Muhammad Anas Ma`arif (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The purpose of this article is to discuss the application of the values of the Adabul 'Alim wal Muta'allim book in the moral formation of the students of SMK NU Palang Tuban. This article uses qualitative research with a case study approach with a single-case design. Methods of data collection using interviews, observation, and documentation. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. Data validity techniques with internal validation, external validation, reliability and objectivity. The results of the study from the application of the values of the book of Adabul 'Alim wal Muta'allim showed that there was a change in morals towards a better direction in accordance with the concept of values in the book, the inhibiting factors for the application of the values of the book of Adabul 'Alim wal Muta'allim were internal and external factors. external. internal factors, namely the lack of student motivation and the existence of different backgrounds and characteristics of students. While external factors come from mistakes in choosing social friends. All of them have been tried to be overcome by the school with various methods and approaches.